Nonlinear Dynamics of Thick Composite Laminated Plates Including the Effect of Transverse Shear and Rotary Inertia - Jweeg, Muhsin J.; Abed Al-wahed, Sameera A; Salih, Wafaa M. (Nahrain University College of Engineering Journal, 2008)
In this work, a suggested analytical solution for nonlinear dynamic analysis of (fiber-reinforced) composite laminated thick plate is developed by using first-ordershear deformation theory (FSDT). A computer program was built for this purpose for antisymmetric cross-ply and angle-ply, simply supported thicklaminated plate and the developed equations are solved by using (MATLAB V.7) program. The finite-element solution is also adopted using (ANSYS V.8) package, to confirm the analytical results. The results presented show the effect of plate thickness-to-side ratio (h/a), aspect ratio (a/b), number oflayers (N), the degree of orthotropic ratio (E1/E2), fiber orientation, boundary conditions, lamination scheme, and the effect of shear deformation and rotary inertia on thethick laminated plate.